EVALUATION OF A THAI READING AND WRITING SKILLS PROMOTION PROGRAM TO ENHANCE ACADEMIC QUALITY IN SMALL-SIZED SCHOOLS: A CASE STUDY OF WAT KHAO YI SAN (PRAMUKVEJKIT) SCHOOL, SAMUT SONGKHRAM PROVINCE - Datesong, Tippawan; Ueatrirat, Ronnayut (Journal of Education and Innovation, 2026)
This study adopted an evaluation research design with two primary objectives: (1) to evaluate a project aimed at promoting Thai reading and writing skills in order to enhance the academic quality of a small-sized school—Wat Khao Yi San (Pramukvejkit) School, Samut Songkhram Province - using the CIPPIEST evaluation model; and (2) to propose development guidelines for projects designed to promote Thai reading and writing skills for improving the academic quality of small-sized schools. The target group comprised of project coordinators, school administrators, teachers, students, and parents, selected through purposive sampling. The research instruments included a project evaluation questionnaire, a teacher teaching self-efficacy assessment, open-ended questionnaire and pre-test and post-test instruments for Thai language courses. Data were analyzed through criterion-referenced evaluation and descriptive statistics, percentage, mean, standard deviation, content analysis. The results indicated that the context dimension was rated at the highest level of appropriateness. The input and process dimensions, as well as the product dimension - encompassing impact, effectiveness, sustainability, and transportability - were rated at a high level across all aspects. Overall, the project evaluation demonstrated a high level of appropriateness and met the established evaluation criteria. With regard to project development guidelines, three key dimensions were identified. In terms of context, the project should articulate clear objectives and goals aligned with stakeholder needs, be appropriate to the school context, and respond to academic quality development policies consistent with the school’s vision and policy framework. Concerning inputs, appropriate determination of content and activity timelines is essential, with careful consideration given to project readiness and capacity, the availability of instructional media, materials, equipment, facilities, and the adequacy of budget allocation. Regarding the process dimension, the project should maximize stakeholder participation and foster collaboration among all stakeholders, including administrators, teachers, students, parents, and the community.